The argument from variation against using one’s own intuitions as evidence - Goh, Esther (2020)
In philosophical methodology, intuitions are used as evidence to support philosophical theories. In this paper, I evaluate the skeptical argument that variation in intuitions is good evidence that our intuitions are unreliable, and so we should be skeptical about our theories. I argue that the skeptical argument is false. First, variation only shows that at least one disputant is wrong in the dispute, but each disputant lacks reason to determine who is wrong. Second, even though variation in intuitions shows that at least one disputant has the wrong intuition in the thought experiment, it is not evidence of unreliability of any disputant’s intuition regarding the philosophical theory being tested. So, variation in intuitions is not good evidence that one’s own intuitions are unreliable. One reply from the literature in peer disagreement is that we should conciliate if we cannot determine who is wrong. I argue that these disagreements are instead unconfirmed peer disagreements (i.e., no good reason to take or dismiss disputants as an epistemic peer, inferior or superior). I argue that if you have a strong intuition about a case, then it is rational for you to remain steadfast. Thus, variation in intuitions does not call for skepticism.